Global, regional, and national burden and trends of Low back pain in middle-aged adults: analysis of GBD 1990–2021 with projections to 2050 - Chuan Zhang; Lanyan Qin; Fuqiang Yin; Qi Chen; Shuna Zhang (BMC Musculoskeletal Disorders)
Abstract Objective This study aims to systematically evaluate the burden of low back pain(LBP) in the middle-aged population across global regions and between genders, assess the major risk factors and their impacts, and project the burden to 2050, providing a scientific basis for global preventive actions. Methods This study utilized The Global Burden of Disease(GBD) 2021 database. First, we integrated the population data of the 45–49, 50–54, and 55–59 age groups provided by the GBD using a weighted average method to calculate the Disability-adjusted life years(DALYs) rate for the middle-aged population aged 45 to 59 years. Subsequently, we analyzed the trends in the burden of LBP globally and across regions from 1990 to 2021, with a focus on stratified data by country, risk factors (e.g., high BMI), and gender. Finally, we employed the Bayesian Age-Period-Cohort(BAPC) model to predict future trends in LBP burden from 2021 to 2050. Results Globally, from 1990 to 2021, the DALY rate for the 45–59 age group with LBP decreased from 875.45(95%UI: 534.57-1340.68) per 100,000 people to 747.92 (450.55-1,161.66), with an EAPC of -0.46 (95%UI: -0.50 to -0.43). Despite the decline in DALY rates, the total number of DALYs due to LBP increased from 5,515,080.64 (95%UI: 3,367,626.11–8,445,931.67) in 1990 to 9,816,401.64 (95%UI: 5,913,142.33–15,249,187.03) in 2021, a rise of 4,301,321. High Socio-Demographic Index (SDI) regions were the most affected, with a DALY rate of 933.03 (95%UI: 557.90–1,420.60) per 100,000 in 2021. Among risk factors, high BMI showed the most significant increase, with DALY rates rising from 153.64 (95%UI: 15.94–334.63) per 100,000 in 1990 to 209.09 (95%UI: 22.16–452.58) in 2021, and an EAPC of 1.08 (95%UI: 1.02 to 1.14). Gender differences revealed a DALY rate of 705.39 (95%UI: 431.21–1,078.96) per 100,000 for males and 803.62 (95%UI: 471.69–1,266.63) per 100,000 for females in 2021. Projections based on the BAPC model suggest that by 2050, global DALYs due to LBP will increase to 11,626,643.07, with females expected to account for 6,725,763.24 and males for 4,900,879.84, indicating a greater burden for females. Conclusion This study highlights the global burden and trends of LBP in the middle-aged population. Although the DALY rate for the 45–59 age group decreased from 1990 to 2021, the total number of DALYs increased significantly due to population aging. In this context, the burden of LBP in low-middle SDI regions has remained largely unchanged and remains substantial, while high-SDI regions, despite some decline, continue to bear the highest overall burden. High BMI continues to contribute significantly to the rising LBP burden, particularly in middle-aged populations, and demands urgent attention. Gender differences indicate that females bear a greater LBP burden than males, with the gap widening over time. Effective preventive and intervention measures are urgently needed to mitigate the future burden of LBP.